Association between dietary vitamin D intake and low muscle mass in US adults: results from NHANES 2011–2018 - Tong, Ye; Teng, Yilin; Peng, Xiaoming; Wan, Bocheng; Zong, Shaohui (Frontiers in Nutrition, 2024)
To investigate the association between dietary vitamin D intake and low muscle mass (LMM) in a representative ad ult population, accounting for total energy intake and other potential confounders.This cross-sectional study utilized data from the National Health and Nutrition Examination Survey (NHANES) involving 8,443 participants. Dietary vitamin D intake was assessed using 24-hour dietary recalls, and LMM was defined based on appendicular lean mass (ALM) adjusted for body mass index (BMI). Multivariable logistic regression models were used to examine the association between quartiles of dietary vitamin D intake and the odds of LMM, adjusting for age, gender, race/ethnicity, BMI, total energy intake, and additional covariates.In Model 1, after adjusting for age, gender, race/ethnicity, BMI, and poverty-to-income ratio, participants in the highe st quartile of vitamin D intake had an odds ratio (OR) of 0.54 (95% CI: 0.37-0.79) compared to the lowest quartile, with a p for trend < 0.001. In Model 2, after further adjustment for total energy intake and several covariates, the association was a ttenuated but remained borderline significant (p for trend = 0.051). In Model 3, after adjusting for additional health-related fa ctors, the OR for the highest quartile was 0.70 (95% CI: 0.47-1.05), with a significant p for trend of 0.029.Conclusions: This study suggests that higher dietary vitamin D intake may be associated with a reduced risk of LMM. Furth er longitudinal research is needed to confirm these findings and explore potential interactions between vitamin D and other di etary factors in muscle mass preservation.